Leveraging strong social ties among young men in Dar es Salaam: A pilot intervention of microfinance and peer leadership for HIV and gender-based violence prevention. Issue 10 (25th November 2016) - Maman, Suzanne; Kajula, Lusajo; Balvanz, Peter; Kilonzo, Mrema; Mulawa, Marta; Yamanis, Thespina
ABSTRACT: Gender inequality is at the core of the HIV patterns that are evident in sub-Saharan Africa. Gender-based violence (GBV) and lack of economic opportunity are important structural determinants of HIV risk. We piloted a microfinance and health promotion intervention among social networks of primarily young men in Dar es Salaam. Twenty-two individuals participated in the microfinance component and 30 peer leaders were recruited and trained in the peer health leadership component. We collected and analysed observational data from trainings, monitoring data on loan repayment, and reports of peer conversations to assess the feasibility and acceptability of the intervention. Eighteen of the loan recipients (82%) paid back their loans, and of these 15 (83%) received a second, larger loan. Among the loan defaulters, one died, one had chronic health problems, and two disappeared, one of whom was imprisoned for theft. The majority of conversations reported by peer health leaders focused on condoms, sexual partner selection, and HIV testing. Few peer leaders reported conversations about GBV. We demonstrated the feasibility and acceptability of this innovative HIV and GBV prevention intervention. The lessons learned from this pilot have informed the implementation of a cluster-randomised trial of the microfinance and peer health leadership intervention.